Aplicação de imunossensor piezoelétrico para identifição de anticorpos contra Leishmania infantum em soro felino - Monteiro, Joseane Rodrigues (2022)
The diagnosis of feline leishmaniasis remains a public health challenge due to the lack of specific protocols for cats. The application of biosensors as an analytical tool has been a favorable alternative. Thus, this study proposed the development of a piezoelectric immunosensor for the qualitative detection of anti-Leishmania infantum A2 antigen antibodies in feline serum. Recombinant protein A2 from L. infantum was used as antigen and feline serum known to be positive was used as a sample. A quartz crystal microbalance with dissipation monitoring was used to carry out the tests based on two immobilization protocols: simple adsorption and self-assembled monolayer (SAM) of the thiol type implemented by carbon disulfide (CS2). Nanogravimetric measurements were performed using specific software, generating a real-time graph. The analytical response of each immunosensor was evaluated by varying the frequency as a function of time before and after the addition of the sample. The biorecognition capacity of the immunosensor was tested by incubating a feline serum sample positive for visceral leishmaniasis, being considered positive in the immunosensor by decreasing the sensor's resonance frequency. The results obtained by the analysis of the reactivity of immunosensors prepared by both simple adsorption and CS2-mediated SAM demonstrated a pattern of response indicative of detection of anti-A2 antigen antibodies present in feline serum from the immobilization of L. infantum recombinant A2 antigen , generating perspectives on the potential for application in the screening of serological samples of cats in endemic areas, which may help to understand their participation in the epidemiology of visceral leishmaniasis and, consequently, contribute to its monitoring and control, being a promising tool to support epidemiological and diagnostic studies of the disease in felines.